2012
DOI: 10.1038/jid.2011.356
|View full text |Cite
|
Sign up to set email alerts
|

CXCR4 Antagonist AMD3100 Accelerates Impaired Wound Healing in Diabetic Mice

Abstract: The antagonism of CXC-chemokine receptor 4 (CXCR4) with AMD3100 improves cardiac performance after myocardial infarction by augmenting the recruitment of endothelial progenitor cells (EPCs) from the bone marrow to the regenerating vasculature. We investigated whether AMD3100 may accelerate diabetes-impaired wound healing through a similar mechanism. Skin wounds were made on the backs of leptin-receptor–deficient mice and treated with AMD3100 or saline. Fourteen days after treatment, wound closure was significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(83 citation statements)
references
References 48 publications
4
74
0
Order By: Relevance
“…In the past, AMD3100, either by itself or in combination with platelet-derived growth factor or tacrolimus (Allen et al 2014;Lin et al 2014), improved wound healing and scar formation in diabetic mice (Nishimura et al 2011) and mice receiving thermal burns (Avniel et al 2005). Here we show that AMD3100 treatment promotes tissue regeneration and restores normal tissue structure and function after injury in a scarless manner.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, AMD3100, either by itself or in combination with platelet-derived growth factor or tacrolimus (Allen et al 2014;Lin et al 2014), improved wound healing and scar formation in diabetic mice (Nishimura et al 2011) and mice receiving thermal burns (Avniel et al 2005). Here we show that AMD3100 treatment promotes tissue regeneration and restores normal tissue structure and function after injury in a scarless manner.…”
Section: Discussionmentioning
confidence: 99%
“…We review here the studies that have identified the molecular pathways regulating the translocation of c-kit-positive CPCs in view of the critical role that cell movement has in stem cell aging and the development of the cardiac senescent dysfunctional phenotype. Stromal cell-derived factor 1 (SDF-1), also known as C-X-C motif chemokine 12 (CXCL12), is a ubiquitously expressed cytokine, critically involved in the trafficking of hematopoietic (5,85,86,188,189) and nonhematopoietic (1,52,60,68,212,219,227,243,350) stem cells. Mice deficient for SDF-1 or its G-protein coupled receptor CXCR4 die perinatally due to defects in hematopoiesis, neurogenesis, vasculogenesis, and cardiogenesis (17,211,237,316,360).…”
Section: Cpc Mobilization In Response To Myocardial Injurymentioning
confidence: 99%
“…Another study found SDF-1 expression was increased in fibroblasts and blister fluid in burn wounds (Avniel et al, 2006). However, the role of SDF-1 in wound healing is not yet clear, and its role in keloids has not yet been investigated (Avniel et al, 2006;Gallagher et al, 2007;Nishimura et al, 2012;Sarkar et al, 2011).…”
Section: Introductionmentioning
confidence: 96%